REPRODUKSI DAN PERKEMBANGBIAKAN TERNAK BABI DI DUSUN AMA-ORI DESA PASSO, KECAMATAN BAGUALA, KOTA AMBON - Labetubun, Jusak; Souhoka, Demianus F.; Sarfan, Riri; Liur, Isye J. (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2024)
Community Service Activities aim to 1) Increase knowledge by educating pig farmers about good practices in reproduction and breeding management to increase animal production and welfare. 2) Teaching various practical skills to farmers, 3) Introducing management practices that pay attention to animal welfare in the aspects of reproduction and breeding, 4) Optimizing pig reproduction to increase farmer productivity and income. Activities using methods; counseling (workshops), development of educational materials, individual consultations, field assistance and use of information technology. The activity lasted for 1 day involving 22 pig breeders in Ama Ori hamlet, Passo Village, Ambon City. The results achieved are the acquisition of a number of knowledge and skills regarding good practices in the field of reproduction and breeding of pigs.